Teachers Professional Development and Content Delivery in Public Senior Secondary Schools in Rivers State - Lily Adonye Hart (IIARD INTERNATIONAL JOURNAL OF ECONOMICS AND BUSINESS MANAGEMENT, 2026)
The study investigated teachers’ professional development and instructional delivery in public senior secondary schools in Rivers State. Three objectives were formulated and translated into corresponding research questions and hypotheses. The study adopted a correlational research design. The population for this study was 6,557 teachers in the 302 public senior secondary schools in Rivers State The sample for this study consisted of 984 teachers. The teachers were stratified into male and female groups. The sample size was determined using 15% of the total population of the study. The instrument that was used for data collection is a self-constructed questionnaire titled Teachers’ Professional Development and Instructional Delivery Questionnaire (TPDIDQ). To determine the reliability of the instrument, the completed copies of the questionnaire were analyzed for reliability using Cronbach Alpha method which yielded reliability coefficients of 0.81, 0.83, and 0.88 with an average reliability coefficient of 0.85 which showed the instruments were reliable. The data collected for the study were analyzed using Pearson’s Product Moment Correlation Coefficient (PPMCC) formula. Research questions were answered based on the value and direction of the correlation coefficient while hypotheses were tested for significance of relationship at 0.05 level of significance. This was further tested by transforming the coefficient of correlation (r) to t in order to establish the significance or otherwise of the r – value. The study found that there is a moderate positive relationship between workshops and instructional delivery in public senior secondary schools in Rivers State. It concluded that by establishing clear, consistent, and evidence-based professional development criteria, school administrators can create an environment that supports teachers’ continuous growth and motivation. This, in turn, can result in better instructional practices, improved student engagement, and overall educational outcomes. It recommended among others that schools should organize frequent workshops focusing on contemporary teaching methods and instructional strategies to improve teachers' content delivery skills.